Case Report: Disseminated Nocardiosis Caused by Nocardia vulneris in a Patient With Macroglobulinemia - Qiu, Fulan; Ma, Zhiyi; Zhong, Rongrong; Huang, Haonan; Wang, Yuehua; Liu, Hui (Frontiers in Public Health, 2022)
This report describes a case of disseminated nocardiosis, caused by Nocardia vulneris, in a 61-year-old man with macroglobulinemia and presenting with repeated fever, cough, shortness of breath, and muscle pain. The isolated Nocardia strain was resistant to ciprofloxacin, but susceptible to amikacin, gentamicin, tobramycin, linezolid, trimethoprim-sulfamethoxazole, amoxicillin/clavulanic, moxifloxacin, ceftriaxone, cefotaxim, and imipenem. The patient was started on combined meropenem and doxycycline treatment, followed by trimethoprim-sulfamethoxazole, which was subsequently switched to a combination treatment of linezolid, amikacin, and trimethoprim-sulfamethoxazole. The patient recovered, and his condition remained stable. Although infection by Nocardia vulneris is rare, and it is easy to miss detection in clinical practice, clinicians should be aware of the possibility of this infection. In addition, the MIC value of the drug sensitivity test should be ascertained when there is a wide choice of medicines. The current case was treated successfully with linezolid, amikacin, and trimethoprim-sulfamethoxazole. In cases of disseminated nocardiosis, the patient should be treated with antimicrobial therapy for at least 12 months. Furthermore, bacteriological examination and antimicrobial susceptibility testing should be performed regularly.